Enhancing Virtual Walking Sensation Using Self-Avatar in First-Person Perspective and Foot Vibrations - Matsuda, Yusuke; Nakamura, Junya; Amemiya, Tomohiro; Ikei, Yasushi; Kitazaki, Michiteru (Frontiers in Virtual Reality, 2021)
Walking is a fundamental physical activity in humans. Various virtual walking systems have been developed using treadmill or leg-support devices. Using optic flow, foot vibrations simulating footsteps, and a walking avatar, we propose a virtual walking system that does not require limb action for seated users. We aim to investigate whether a full-body or hands-and-feet-only walking avatar with either the first-person (Experiment 1) or third-person (Experiment 2) perspective can convey the sensation of walking in a virtual environment through optic flows and foot vibrations. The viewing direction of the virtual camera and the head of the full-body avatar were linked to the actual user’s head motion. We discovered that the full-body avatar with the first-person perspective enhanced the sensations of walking, leg action, and telepresence, either through synchronous or asynchronous foot vibrations. Although the hands-and-feet-only avatar with the first-person perspective enhanced the walking sensation and telepresence, compared with the no-avatar condition, its effect was less prominent than that of the full-body avatar. However, the full-body avatar with the third-person perspective did not enhance the sensations of walking and leg action; rather, it impaired the sensations of self-motion and telepresence. Synchronous or rhythmic foot vibrations enhanced the sensations of self-motion, waking, leg action, and telepresence, irrespective of the avatar condition. These results suggest that the full-body or hands-and-feet avatar is effective for creating virtual walking experiences from the first-person perspective, but not the third-person perspective, and that the foot vibrations simulating footsteps are effective, regardless of the avatar condition.